Extra-peritoneal vs. Trans-peritoneal Radical Cystectomy pros and cons - Allameh, Farzad; Eslami, Amir Hossein (Urology Journal, 2024)
One of the most common cancers of the urinary tract is bladder tumors. Bladder cancers are divided into two groups: non-muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer. (1) Trans-Peritoneal Radical Cystectomy (RC) with pelvic lymphadenectomy is the standard technique in muscle invasive and high risk non-muscle invasive bladder cancer (2). and Urologist around the world are more familiar with trans-peritoneal technique. In some articles extra-peritoneal Radical Cystectomy (RC) implied as an decreased postoperative complications techniques. In this letter we want to compare these two techniques and find out the pros and cons of these techniques.